Tax Avoidance Determinants of Earning Management - Siska; Nursida, Nina; Astuti, Eni Dwi (International Journal of Science and Society, 2024)
This research seeks to empirically explore the impact of Other Comprehensive Income, Financial Distress, Tax Avoidance, and Free Cash Flow on Earnings Management among Real Estate and Property firms listed on the Indonesia Stock Exchange during the period spanning 2019 to 2021. Employing a approach quantitative, the research utilizes multiple linear regression analysis conducted through SPSS 26 as the analytical tool. Through purposive sampling from a total population of 60 companies, 43 entities meeting the specified criteria were chosen as the sample. The findings reveal that while Other Comprehensive Income, Financial Distress, and Free Cash Flow do not exert a significant influence on earnings management, tax avoidance emerges as a notable factor impacting earnings management.